Delayed Exposed Secondary Skin Grafting - P. K. Bilwani (Indian Journal of Plastic Surgery)
A series of 125 cases of granulating raw areas of different aetiology treated by delayed exposure method of secondary skin grafting is presented. The advantages of the technique have been outlined.